Impact of Sociodemographic factors on prevalence of overweight and obesity among adolescents of urban Meerut - Jain, Bhavan; Jain, Seema; Chopra, Harivansh; Garg, Sunil Kumar; Singh, Ganesh; Mittal, Chhaya (Indian Journal of Community Health, 2018)
Background: Adolescent obesity is becoming a major public health problem in urban areas of India and its prevalence is increasing in all socioeconomic groups irrespective of religion, region and caste. Aims & Objectives: To find out prevalence of overweight & obesity among adolescents and to study its association with sociodemographic factors. Material & Methods: This cross-sectional study was carried out in the area covered by Urban Health and Training Centre of Lala Lajpat Rai Memorial Medical College, Meerut. Sample size was estimated by keeping the prevalence as 10% with 95% confidence interval and relative precision of 20%. A total of 872 adolescents were selected randomly using proportional allocation method. Results: The prevalence of overweight was found to be 17.4% and obesity 6.9%. The prevalence was significantly higher among females and in those belonging to nuclear families as well as higher socioeconomic status. Conclusion: The prevalence of overweight and obesity is quite high in the urban area and there is a need to develop an effective programme for the prevention of obesity in these areas.